1983
DOI: 10.1111/j.1751-1097.1983.tb04495.x
|View full text |Cite
|
Sign up to set email alerts
|

STATE I‐STATE II TRANSITIONS IN THE THERMOPHILIC BLUE‐GREEN ALGA (CYANOBACTERIUM) Synechococcus lividus*

Abstract: Time courses of state I‐state II transitions were measured in the thermophilic blue‐green alga (Cyanobacterium), Synechococcus lividus, that was grown at 55°C. The rate of the state I–II transition using light II illumination was the same as that in the dark, and the dark state was identified to be state II. Therefore, light regulation attained by state transitions is produced by the state II–I transition induced by system I light. The redox level of plastoquinone did not affect this dark state II. Arrhenius p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
68
2

Year Published

1986
1986
2015
2015

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 20 publications
8
68
2
Order By: Relevance
“…This apparent difference in energy transfer efficiency may be related to a difference in energy transfer states. Dark-adapted wild-type cells are in state 2 (Fork and Satoh, 1983), with inefficient energy transfer between the phycobilisome and PSll (Mullineaux et al, 1990). In contrast, dark-adapted PSI-less cells appear to be in state 1.…”
Section: Fluorescence Spectramentioning
confidence: 95%
“…This apparent difference in energy transfer efficiency may be related to a difference in energy transfer states. Dark-adapted wild-type cells are in state 2 (Fork and Satoh, 1983), with inefficient energy transfer between the phycobilisome and PSll (Mullineaux et al, 1990). In contrast, dark-adapted PSI-less cells appear to be in state 1.…”
Section: Fluorescence Spectramentioning
confidence: 95%
“…3). At 77K, PSII gives rise to fluorescence emission at 685 and 695 nm, whereas PSI gives emission at 720 nm, Variations in the emission ratio F720/F695 have consistently been used to demonstrate changes in excitation energy distribution after light state adaptation [1,10,19,20], and from Fig, 3 the decrease in this ratio observed upon incubation in the light in the presence of ATP is consis. Table I tent with d¢~:r~,~¢d energy transfer to PSII or lncreawd spillover of energy rrom PSii to PSI, Previt~u~ly observed Iiilht.lndu~ed chanwes in the ratio F720/F695 occurrin~ in isolated membrane systems have been Interpreted as due to reversible pholooxidation of chlorophyll [13,13], Tl~is interpretation is not possible for the erfects observed here, since, the increase in the ratio FT101F693 observed upon transition from light to dark was abolished by the inclusion of sodium fluoride, sugttesting thal this redistribution of excitation energy requires the activity or a membrane.bound phosphatase, Pr~lncubation with FSBA partly inhibited the Increase in F7201F695 observed upon incubation in the light, implytn8 the requirement for a kinase activity in the light.induced redistribution of excitation energy, From this study it seems evident that reversible phosphorylation of at least one polypeptide of mass 15 kDa occurs specifically under plastoqulnone-reduclnlt~ conditions known to give rise to State 2, "The phosphorylation of all species of polypeptide with the exception of that with mass 18.5 kDa w~.s inhibited by a kinase inhibitor and phosphorylation was maintained tinder otherwise dephosphorylating conditions by a non-specific phosphatase inhibitor.…”
Section: Thereby Inducing Its Dissociationmentioning
confidence: 99%
“…PBS can transfer energy to both photosystem II (PSII) and photosystem I (PSI) [2], and energy distribution between PSII and PSI is regulated by a process called state transition [23,24]. Early reports showed that state transitions occurred in a time range of subseconds to seconds [25] and that this process is controlled by the redox state of electron carriers between PSI and PSII [26].…”
Section: Introductionmentioning
confidence: 99%